WHY RIFTS INVERT IN COMPRESSION - Hansen D.L.; Nielsen S.B. (My University, 2003)
The common observation of sedimentary basin inversion in orogenic forelands implies that rifts constitute weak areas of the continental lithosphere. When compressed, the rifts respond with uplift of the deepest parts and erosion of sediments therein. Simultaneously, syn-compressional marginal troughs are formed flanking the inversion zone.Since rifting and subsequent post-rift thermal re-equilibration are processes expected to alter the long-term mechanical state of the lithosphere, the phenomenon of basin inversion is non-trivial from a rheological point of view. Stochastic modelling of the long-term thermal structure beneath sedimentary basins indicates that the crustal part of a rift is warmer, and hence weaker, than the surrounding crustal blocks. In contrast, the mantle part is cold and strong beneath the basin centre.In this paper, it is investigated whether the rifting-induced strength alterations constitute a sufficient condition for a thermally equilibrated rift to invert by compression. Numerical experiments with two-dimensional dynamic thermo-mechanical models are performed. In particular, the focus is on rifting-related mechanical instabilities that reduce the load bearing capacity of the lithosphere. In the experiments, strain-softening behaviour is introduced in the non-associated plasticity model representing brittle yielding. The result is self-consistent large-scale fault formation.The models predict that the rifting-related necking instability induces differential crustal thinning increasing the post-rift crustal weakness. Strain softening and the associated fault formation amplifies the necking instability and introduces zones of structural weakness exposed for compressional re-activation.Under these circumstances, basin inversion follows as a natural consequence of rift compression.
Keywords: BASIN INVERSION; CONTINUUM MECHANICS; INSTABILITIES; NECKING; STRAIN SOFTENING